Impact of duration of occupational exposure on physical and mental health of construction workers in Lahore, Pakistan (Journal of Fatima Jinnah Medical University, 2022)
Background: Construction industry is one of the most hazardous and accident prone occupation causing around 270 million accidents and 2 million deaths annually. In Pakistan reporting of incidence of occupational injuries and accidents is low. The present study aimed to determine the physical and mental health profile of construction workers in Lahore, Pakistan.Subjects and methods: An analytical cross-sectional study was conducted among construction workers in Lahore from January 2020 to September 2020. The study included 181 participants by using non-probability convenience sampling technique. Data was collected by using a self-structured, pre-tested questionnaire. Data was analyzed using SPSS version 23. Chi-square test was applied and p-value
Keywords: Construction workers; Physical health; Mental health; Occupational injuries